The effect of storage temperature and time on total phenolics and enzymatic activity of sapodilla (Achras sapota L.) (2016)
The tropical fruits are sensitive to low storage temperatures, so optimal parameters have been searched for storage and transport for the purpose of maintaining its overall quality as long as possible to the consumer. The effect of different storage temperatures (6, 10, 15, 21 and 27 ºC) and storage durations (0 to 20 d) on total phenolics and enzymatic activity of peroxidase (POD), catalase (CAT), and polyphenol oxidase (PPO) on sapodilla (Achras sapota L.) fruit was investigated. The extraction and quantitation of protein and phenols from fruit was performed, then the enzymatic activity of PPO, POD and CAT was determined. The concentration of total phenolics decreased in the control fruit. POD activity was 3268.7 ± 1.4 U g-1 in ripening and senescence of sapodilla stored at 27 °C. CAT activity reached a peak of 34.0 ± 0.25 U g-1 in senescence in control fruit. PPO activity remained unchanged in the ripening stage and until consumption. The best storage temperatures to prolong the post-harvest life of the sapodilla fruit were 6 °C and 10 °C when storage was at low temperatures. POD activity was inactivated during sapodilla storage at low temperatures (6 and 10 °C) and after being transferred to 27 °C the activity was reactivated. Likewise of fruits stored at 21 °C after being transferred to 27 °C the POD activity was reactive with a maximum value of 46.3 ± 0.012 U g-1. Enzyme activity decreased at low temperatures, which contributed to the preservation of the fruit, showing that the cold retards the maturation processes.